History of the FGBI “ARRIAH” international cooperation on foot-and-mouth disease (on occasion of the 65th anniversary of the Institute) - V. М. Zakharov (Ветеринария сегодня)
The paper covers the long history of the FGBI “ARRIAH” international cooperation on foot-and-mouth disease, starting from 1964 when its name was the All-Union-Foot-and-Mouth Disease Research Institute. Foot-and-mouth disease was the main focus of the Institute’s research activities. Under of the auspices of the Institute,a Coordination Board was established. It consisted of the specialists of the veterinary services, research and educational institutions from all the republics of the USSR.A common research programme aimed at the development and implementation of effective tools and methods for FMD control was worked out. The next stage of international cooperation was related to the functioning of the Council for Mutual Economic Assistance (CMEA or COMECON). Starting from 1977, the Institute coordinated the CMEA member countries’ research activities on 11 topics of the FMD issue, held meetings on the subject, as well as meetings of the Board of Commissioners.After formation of the Commonwealth of Independent States (CIS), the Institute developed the long-term “Programme of joint activities of the CIS member states for the prevention and control of foot-and-mouth disease in the CIS member states” (2004). Later on, the Programme was repeatedly altered and extended to address new priorities, with the Institute undertaking the coordinating role. The “Set of joint measures of the CIS member states for the prevention and control of foot-and-mouth disease for the period up to 2025” has now been adopted, and the FGBI “ARRIAH” also performs the functions of the basе organization of the CIS member states for the advanced training and retraining in animal disease diagnosis and control. At present, much of the FGBI “ARRIAH” international cooperation on FMD takes place through its acting as the WOAH Reference Laboratory for Foot-and-Mouth Disease and the FAO Reference Centre for Foot-and-Mouth Disease.